Impact of a legislated human right on poverty reduction in Mexico - Matallana Villegas, Silvia (DIXI, 2024)
The constitutionalization of the universal right to a pension for the elderly is evidence that the Mexican Congress is in a position to promote sound legislation in accordance with human rights. In doing so, it fulfills its main function of promoting welfare, maximizing general utility by reducing poverty levels in the population. It also protects the most vulnerable minorities. However, in order to fulfill this purpose, the legislature must not only insert the rights in the legislation, but also specify precise standards to guarantee them through an effective materialization, expressing their content in detail and thus facilitating their enforceability.
Keywords: Human rights; legislature; elderly pension; non-contributory pensions; poverty